Relationship between age and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage requiring invasive mechanical ventilation: a secondary analysis - Qing-qing Wu; Wei-wen Chen; Tian-lai Lin; Cun-rong Chen; Zhi-rong Ding; You-li Chen (Scientific Reports)
Abstract The association between age and delayed cerebral ischemia (DCI) has long been controversial. This study aimed to explore the relationship between age and DCI in patients with aneurysmal subarachnoid hemorrhage (aSAH) requiring invasive mechanical ventilation (IMV). This study reanalyzed previously published data from a French university hospital. Chalard K et al. conducted a retrospective cohort study in the intensive care unit from 2010 to 2015. Univariate and multivariate logistic regression analyses were employed to identify risk factors for DCI. The non-linear relationship between age and DCI was estimated through a restricted cubic spline regression, and a two-piecewise linear regression model was further performed to calculate the threshold effect. The analysis included 222 patients with aSAH requiring IMV. Their median age was 56 years (range 19–84 years). Patients were equally divided into four groups: Q1 (19–45 years), Q2 (46–55 years), Q3 (56–63 years), and Q4 (64–84 years). The incidence of DCI was 27.48% (N = 61). After adjustment for potential confounders, patients in group Q2 were found to be more likely to develop DCI [odds ratio (OR), 4.91; 95% Confidence Interval (CI), 1.53–15.70] compared to those in group Q1. After adjusting for confounding variables, for patients aged < 53 years, the risk of DCI increased by 14% (OR, 1.14; 95% CI 1.05–1.23) for each 1-year increase in age. For patients aged 53 to 77 years, the risk of DCI decreased by 19% (OR, 0.81; 95% CI 0.73–0.88) for each 1-year increase. For patients aged > 77 years, the risk of DCI did not decrease with increasing age (OR, 1.42; 95% CI 0.47–4.34). Age was non-linearly associated with DCI in patients with aSAH requiring IMV.